Chromosomal Abnormalities in Allium cepa Induced by Treated Textile Effluents: Spatial and Temporal Variations - W. M. Dimuthu Nilmini Wijeyaratne; P. G. Minola Udayangani Wickramasinghe (Journal of Toxicology)
Appropriate effluent treatment processes are expected to significantly reduce the toxicity of effluents before they are released to the natural environment. The present study was aimed to assess the spatial and temporal variations of the physical and chemical water quality parameters of a natural water body receiving treated textile effluents and to assess the chromosomal abnormalities induced by the treated textile effluents. Four sampling sites (A: effluent discharge point; B: 100 m downstream from site A along the tributary; C: 200 m downstream from site A along the tributary; D: 100 m upstream from site A along the tributary) were selected associated to a tributary that received treated textile effluent. The physical and chemical water quality parameters were measured in the composite water samples collected from the study sites, and Allium cepa bioassay was conducted using aged tap water as the control. Sampling was conducted in both rainy and dry seasons. The conductivity, TDS, COD, and colour intensity of the water samples collected from the study sites were significantly higher during the dry season compared to those in the rainy season. Allium cepa root meristematic cells exposed to water samples from sites A, B, and C showed a significantly high interphase and prophase indices compared to those exposed to aged tap water and upstream site during both rainy and dry seasons. The mitotic index of the root tip cells of Allium cepa bulbs exposed to the water samples collected from the effluent discharge point (site A) and from the 100 m downstream site from site A (site B) was significantly lower than that of the other sites in both rainy and dry seasons. However, the mitotic index of the root tip cells of Allium cepa bulbs exposed to the water samples from the upstream site was not significantly different from that of the control treatment during both sampling seasons. The bioassay indicated that the mitotic index and phase index of the root meristematic cells of Allium cepa can be affected by the treated textile effluents released to the water body and the occurrence of C metaphase, chromosomal adherence, bridges, disturbed anaphase, vagrant chromosomes, and chromosomal breaks indicated that the treated textile effluent receiving tributary can possibly contain genotoxic and mutagenic compounds which can induce chromosomal abnormalities.